The Usage of CIDOS and Social Network Sites in Teaching and Learning Processes at Malaysian Polytechnics - Razali, Sharifah Nadiyah; Shahbodin, Faaizah (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
In 21stÂ century learning, students use educational technologies to apply knowledge to new situations, analyse information, collaborate, solve problems, and make decisions.Â Utilising emerging technologies, to provide expanded learning opportunities, is critical to the success of future generations. In this paper, the author will share the findings on the usage of CIDOS and Social Network Sites in teaching and learning processes at Malaysian Polytechnics. Two sets of questionnaires were distributed to a group of 84 diploma students and 41 lecturers from Politeknik Ibrahim Sultan, Politeknik Merlimau, Politeknik Tuanku Syed Sirajuddin, Politeknik Kota Kinabalu, and Politeknik Sultan Idris Shah.The results of the study show the existence of communication and interaction difficulties in existing Learning Management Systems (LMS). As a recommendation for future research, it is suggested to integrate current LMS with Facebook to support Online Collaborative Learning (OCL).